Cytokine and metalloproteinases in gingival fluid from patients with chronic periodontitis - Escalona, Laura A; Mastromatteo-Alberga, Patrizzia; Correnti, María (Investigación Clínica, 2016)
The purpose of the present research was to determine the levels of IL-1Î±, IL1Î², TNF-Î±, IL-6, IL-6sR, IL-8, IL-10, MMP-3 and MMP-8 in gingival crevicular fluid (GCF) of subjects with chronic periodontitis. Clinical measurements were carried out in 20 patients with chronic periodontitis and 11 periodontally healthy controls. The clinical indexes evaluated were: gingival index (GI), plaque index (PI), bleeding on probing (BOP), probing depth (PD) and clinical attachment loss (CAL); the measurements were taken at six sites per tooth in all teeth in each subject. GCF samples were taken from one tooth per quadrant, and the levels of mediators were measured using an ELISA test. Statistically significant differences were observed between patients and control group in relation to all clinical parameters evaluated (p<0.05). The gingival concentrations, in pg/mL, of IL-1Î± (patients: 239.06 Ó 65.5 vs control: 97.79 Ó 15.81), IL-1Î² (patients: 157.19 Ó 36.4 vs control: 63.44 Ó 19.04), TNF-Î± (patients: 10.87 Ó 1.7 vs control: 1.15 Ó 0.84), IL-6 (patients: 3.77 Ó1.7 vs control: 0.43 Ó 0.22), IL-6Sr (patients: 655.59 Ó 185.8 vs control: 73.59 Ó 23.18), IL-8 (patients: 496.3 Ó 155.3 vs control: 206.13 Ó 46.63), IL-10 (patients: 10.75 Ó 3.6 vs control: 2.41 Ó 0.57), MMP-3 (patients: 3531 Ó 1558.2 vs control: 724.84 Ó 289.51) and MMP-8 (patients: 8231.70Ó 1279.2 vs control: 1534.67Ó 814.90) were significantly greater in patients with periodontal disease than in the control group (p<0.001). The higher levels of the cytokines and metalloproteinases obtained in this study were significantly associated with the severity of the periodontal disease